Processing of Acoustic Information in Lexical Tone Production and Perception by Pediatric Cochlear Implant Recipients - Deroche, Mickael L. D.; Lu, Hui-Ping; Lin, Yung-Song; Chatterjee, Monita; Peng, Shu-Chen (Frontiers in Neuroscience, 2019)
Purpose – This study examined the utilization of multiple types of acoustic information in lexical tone production and perception by pediatric cochlear implant (CI) recipients who are native speakers of Mandarin Chinese. Method – Lexical tones were recorded from CI recipients and their peers with normal hearing (NH). Each participant was asked to produce a disyllabic word, yan jing, with which the first syllable was pronounced as Tone 3 (a low dipping tone) while the second syllable was pronounced as Tone 1 (a high level tone, meaning ‘eyes’) or as Tone 4 (a high falling tone, meaning ‘eyeglasses’). In addition, a parametric manipulation in fundamental frequency (F0) and duration of Tones 1 and 4 used in a lexical tone recognition task in Peng et al. (2017) was adopted to evaluate the perceptual reliance on each dimension. Results – Mixed-effect analyses of duration, intensity, and F0 cues revealed that NH children focused exclusively on marking distinct F0 contours, while CI participants shortened Tone 4 or prolonged Tone 1 to enhance their contrast. In line with these production strategies, NH children relied primarily on F0 cues to identify the two tones, whereas CI children showed greater reliance on duration cues. Moreover, CI participants who placed greater perceptual weight on duration cues also tended to exhibit smaller changes in their F0 production. Conclusions – Pediatric CI recipients appear to contrast the secondary acoustic dimension (duration) in addition to F0 contours for both lexical tone production and perception. These findings suggest that perception and production strategies of lexical tones are well coupled in this pediatric CIs population.